The effects of seat tube angle on the metabolic cost during cycling at low intensity workload - Chung, K. R.; Hyeong, J. H.; Kim, S. Y.; Senner, V.; Hoechtl, F. (Procedia Engineering, 2011)
The effects of seat tube angle (STA) on the cycling performance at low intensity were investigated in terms of metabolic cost. Oxygen consumption (VO2), heart rate (HR), ventilation (VE) were measured during cycling at each of three STA (80°, 60°, 40°) and at constant 60° upper body angle using a custom made steady-state ergometer. 12 male untrained students (age 24.5 ± 1.6 years) were recruited and submaximal cycling tests (work load: 35% of individual peak power, cadence: 60 rpm, duration: 30 min) were performed. Measured mean VO2 were 24.6 ± 2.8, 25.2 ± 2.9 and 24.8 ± 2.5 ml/min*kg and mean heart rates were 140.7 ± 10, 132.8 ± 8.8 and 131.7 ± 10.1 beat/min at 80°, 60° and 40° STA, respectively. There was no significant difference on the oxygen consumption but the mean heart rate at 60° and 40° STA was significantly lower than at 80° STA. In conclusion, riding a bicycle at shallow STA is as cost efficient as at steep STA and is better in terms of heart rate which is evaluated to be more suitable postures for casual cycling.